Joint Ventures and Real Options: An Integrated Perspective - CUYPERS, Ilya (Institutional Knowledge at Singapore Management University, 2007)
We provide a comprehensive synthesis and extension of the real option (RO) literature on joint ventures (JVs), contributing in three main areas. First, we examine major alternative theoretical perspectives on JVs - learning, bargaining, transaction cost and agency theory - to elaborate how they complement or contradict RO predictions. Second, we compare arguments and variables used to explain different JV stages - initial RO explicitness and equity shares, JV stability, and performance consequences - and highlight research opportunities. Third, we discuss and extend research about behavioral aspects of making RO (JV) investments. Overall, we offer new predictions and suggestions for a better integration within the RO literature, and between RO and related literatures on JVs.